Measuring sustainable human development indicators in Basra Province in 2023 - Ghaleb Sabah Al – Anbar, Assist. Lect . Saleem (Basra studies journal, 2025)
The research addressed the main sustainable human development indicators (education - health - income) through which the human development index is measured in Basra Governorate and at the district level, then depending on it development plans are drawn up according to the population size and growth. The research also aims to measure sustainable human development indicators and the extent of spatial variation between the districts of Basra Governorate. The Sustainable. This study reveals the reality of sustainable human development indicators and their levels of variation among the districts of Basra Governorate, and to reach the level of human development in the governorate and the extent of the efficiency of the services provided to the population. The researcher concluded that Basra Governorate is within the average level of human development with an index of (0.762) and a deprivation rate of (0.238).